Association between respiratory syncytial virus hospitalization in infancy and childhood asthma. Issue 5 (10th February 2020) - Coutts, Jonathan; Fullarton, John; Morris, Carole; Grubb, ElizaBeth; Buchan, Scot; Rodgers‐Gray, Barry; Thwaites, Richard
Abstract: Introduction: Respiratory syncytial virus infection in early childhood has been linked to longer‐term respiratory morbidity; however, debate persists around its impact on asthma. The objective was to assess the association between respiratory syncytial virus hospitalization and childhood asthma. Methods: Asthma hospital admissions and medication use through 18 years were compared in children with (cases) and without (controls) respiratory syncytial virus hospitalization in the first 2 years of life. All children born in National Health Service Scotland between 1996 and 2011 were included. Results: Of 740 418 children (median follow‐up: 10.6 years), 15 795 (2.1%) had a respiratory syncytial virus hospitalization at ≤2 years (median age: 143 days). Asthma hospitalizations were three‐fold higher in cases than controls (8.4% vs 2.4%; relative risk: 3.3, 95% confidence interval [CI]: 3.1‐3.5; P  < .0001) and admission rates were four‐fold higher (193.2 vs 46.0/1000). Cases had two‐fold higher asthma medication usage (25.5% vs 14.7%; relative risk: 1.7, 95% CI: 1.7‐1.8; P  < .0001) and a three‐fold higher rate of having both an asthma admission and medication (4.8% vs 1.5%; relative risk 3.1, 95% CI: 2.9‐3.3; P  < .0001). Admission rates and medication use remained significantly ( P  < .001) higher for cases than controls throughout childhood (admissions: ≥2‐fold higher; medication: ≥1.5‐fold higher). Respiratory syncytial virus hospitalization was the most significant risk factor for asthma hospitalizations±medication use (odds ratio: 1.9‐2.8; P  < .001). Conclusions: Respiratory syncytial virus hospitalization was associated with significantly increased rates and severity of asthma throughout childhood, which has important implications for preventive strategies.